Mechanism of methicillin-resistant Staphylococcus aureus biofilm degradation by bacteriophages - Dakheel, Khulood Hamid (2018)
Methicillin resistant Staphylococcus aureus (MRSA) is a persistent pathogen responsible for widespread nosocomial infections. A major virulence factor that confers both antimicrobial resistance and pathogenicity is the ability to form protective biofilms that protect the bacterial from the extracellular environment. Biofilms largely render antibiotics and host immune responses ineffective; and are implicated in nearly 80% of all chronic recurring infections. Emerging antibiotic resistance levels in bacteria are becoming an increasingly serious threat to global public health and impact the cost of health care for infectious diseases. Effective action plan and novel antimicrobials are needed to combat the global spread of MRSA. Potential novel antimicrobials are as bacteriophages (bacterial viruses or phages) that have natural predatory antimicrobial potency towards pathogenic bacteria. Although such viruses exist, little is known about predatory antimicrobial mechanisms of these phages in the control of bacterial populations within the biofilm. This study has investigated the potential for phages to be used to target methicillinresistant S. aureus biofilm producers. For this work, MRSA strains were isolated genotypically characterized based on the Staphylococcal protein A gene (spa type) and on biofilm formation. The proteins, exopolysaccharides, extracellular DNA and RNA within the biofilms were evaluated using a biofilm dispersal assay. Additionally, the packed-beads and mechanical disruption process assay were used to characterise the cell-surface adhesions and cohesion, respectively. The data showed that the predominant genotype (22 out of 25 isolates) was the spa type t127. The majority of the isolates were categorized as moderate biofilm producers. The dispersal assay showed that the polysaccharide intercellular adhesin (PIA)-independent mechanism was found in 12 and the remaining 13 isolates were PIA-dependent. Strong biofilm dispersal following (1) RNase and (2) DNase followed by proteinase K treatment was observed for both groups. Differences in dispersal between the isolates with the different mechanisms were seen. However; sodium metaperiodate caused dispersal in PIA-dependent biofilm wheres it stimulated biofilm formation of PIA-independent biofilms. Consequently, the amount of biofilm components and the adhesion and cohesion ability of the bacteria were non-correlated. In some isolates, the biofilm weakened the ability of the cells to adhere onto surfaces but strengthened cell-to-cell cohesion. The efficiency of these isolates to adhere onto glass beads increased after partial removal of the biofilm. It was concluded that nucleic acid and proteins are main components of biofilm matrix of MRSA clone t127 with observed relationship between adhesion and cohesion for biofilm tested. Secondly, promising phage candidates that target the MRSA biofilms were isolated from polluted water. Two phages, UPMK_1 and UPMK_2, were characterized based on one step growth curves, host infectivity, electron microscopy and genome diversity. The phages demonstrated antagonistic infectivity on planktonic cultures. This was further assayed using an in vitro static biofilm assay in microtiter-plates and in vitro visualization of the biofilm architecture in situ by labeling biofilm with two fluorescent stains, SYTO 9 and propidium iodide then performing confocal laser scanning microscopy (CLSM) analysis. Both phages produce halos around the clear zone of lysis on lawns of their specific host. The burst size was 32 PFU/cell for UPMK_1 and 67 PFU/cell for UPMK_2. Host specificity was determined on 25 biofilm producing MRSA. UPMK_1 and phage UPMK_2 can lyse all strains tested. Additionally, phage UPMK_2 can lyse another 25 strain belonging to MRSA ST239; a dominant MRSA strain in Far East countries including Malaysia. Morphologically, phage UPMK_1 is a siphovirus with 55.5 ± 1.5 nm head diameter and 335.9 ± 30.5 nm tail length with diameter 12.8± 1.5 nm. Phage UPMK_2 is a structurally large podovirus with a 110.5±59.8 nm head diameter and 28.3 ± 15.5 nm tail length. UPMK_1 has a genome size of 152788 bp with 155 predicted genes and UPMK_2 has 40955 bp with 62 predicted genes. Biofilm analyses and CLSM revealed that UPMK_1 and UPMK_2 degraded the biofilm after 6 hours and 8 hours, respectively. Phage protein profiles were determined as was the ability of phages to lyse the biofilms based on zymograpic analysis. Phage-host interaction were examined by 2DE protein profiles assessed using a matrix-assisted laser desorption ionization-time-of-flight (MALDI-TOF/TOF) mass spectrometer. In zymogram gels lytic activity for phage UPMK_1 and UPMK_2 on MRSA t127/4 and MRSA t223/20 biofilms, respectively, can be clearly observed. UPMK_2 is most effective as evidenced by four lytic bands compared to UPMK_1 that has a single lytic band. Mass spectrometry analysis for both UPMK_1 and UPMK_2 revealed that each band contains many peptides from several phage proteins. Furthermore, peptides with peptidase activity were predominant. Additionally, it was established that the biofilm lytic proteins in phage UPMK_2 also have lytic activity towards PIA-dependent and independent biofilm of others MRSA biofilm producers whereas UPMK_1 can only lyse its host. MS/MS analysis of the proteins in the biofilms induced in bacteria after phage treatments revealed that the phage infections up-regulated several metabolic pathways including those involved in energy conversion, protein metabolism, nucleotide metabolism and pathways involved in the generation of oxidants and antioxidants. This suggests they are firmly involved in the biofilm degradation. This study has provided significant amount of novel data to address fundamental questions about the biology of MRSA biofilm degradation by phages. It is envisaged that this data will be useful in the development of novel and effective therapeutic for control of the MRSA biofilms.